Feminism - Freedman,Jane (Viva Books, 2002)
What is the relevance of feminist thought to today's society? * What do feminists mean by equality and difference? * Can we find unity in feminist thought, or only conflict? Feminism provides an introduction to some of the major debates within feminist theory and action. Focusing on the perennial question of equality and difference, the book examines the ways in which this has been played out in different areas of feminist social and political theory. Jane Freedman adopts a refreshing approach by focusing on issues rather than schools of thought. Among the subjects she examines are politics and women's citizenship, paid and unpaid employment and the global economy, sexuality and power, and race and ethnicity. Finally, the book analyses the problem of essentialism for feminism and the challenge of postmodern and poststructuralist theories. Written in a jargon-free style, this book presents a clear and concise introduction to a wide range of feminist thought.